2021
DOI: 10.1177/0363546521997097
|View full text |Cite
|
Sign up to set email alerts
|

Change in Posterior Tibial Slope in Skeletally Immature Patients With Anterior Cruciate Ligament Injury: A Case Series With a Mean 9 Years’ Follow-up

Abstract: Background: Increased lateral posterior tibial slope (LPTS) is associated with increased rates of anterior cruciate ligament (ACL) injury and failure of ACL reconstruction. It is unknown if ACL deficiency influences the developing proximal tibial physis and slope in skeletally immature patients through anterior tibial subluxation and abnormal force transmission. Purpose: To assess the natural history of LPTS in skeletally immature patients with an ACL-injured knee. Study Design: Case series; Level of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In previous studies, some researchers believed that MTS could affect the prognosis of patients,[36] whereas others believed that LTS could play a greater role. [12,33,37] In this study, MTS and LTS both were risk factors that increased graft SI. Moreover, we believed that it is inappropriate to separate the MTS and LTS as two independent tibial anatomical factors.…”
Section: Discussionmentioning
confidence: 55%
“…In previous studies, some researchers believed that MTS could affect the prognosis of patients,[36] whereas others believed that LTS could play a greater role. [12,33,37] In this study, MTS and LTS both were risk factors that increased graft SI. Moreover, we believed that it is inappropriate to separate the MTS and LTS as two independent tibial anatomical factors.…”
Section: Discussionmentioning
confidence: 55%
“…The authors found that the posterior slope increased in the ACL-injured knee more than in the contralateral side over the study period. Twenty-two patients had ACL reconstruction during the study period and 16 did not, and the posterior tibial slope was not predictive of surgical intervention 53 .…”
Section: Sportsmentioning
confidence: 92%
“…5,6 Recent studies, however, are emphasizing a mutual influence, as tibial slope has been shown to increase over time in the ACLdeficient, skeletally immature knee. 7 It is hypothesized that altered biomechanics with enhanced posterior force transmission in the ACL-deficient knee may influence the developing physis, leading to altered longitudinal growth and increased tibial slope. In addition to tibial slope, the meniscal geometry, including meniscal bone angle and meniscal slope, have been shown to influence the risk of ACL injury.…”
Section: See Related Article On Page 2582mentioning
confidence: 99%